Listeria monocytogenes Biofilm Adaptation to Different Temperatures Seen Through Shotgun Proteomics - Santos, Tiago; Viala, Didier; Chambon, Christophe; Esbelin, Julia; Hébraud, Michel (Frontiers in Nutrition, 2019)
Listeria monocytogenes is a foodborne pathogen that can cause invasive severe human illness (listeriosis) in susceptible patients. Most human listeriosis cases appear to be caused by consumption of refrigerated ready-to-eat foods. Although initial contamination levels in foods are usually low, the ability of these bacteria to survive and multiply at low temperatures allows it to reach levels high enough to cause disease. This study explores the set of proteins that might have an association with L. monocytogenes adaptation to different temperatures. Cultures were grown in biofilm, the most widespread mode of growth in natural and industrial realms. Protein extractions were performed from three different growth temperatures (10°C, 25°C and 37°C) and two growth phases (mid-log and early stationary). L. monocytogenes subproteomes were targeted using three extraction methods: trypsin-enzymatic shaving, biotin-labelling and cell fractionation. The different subproteomes obtained were separated and analyzed by shotgun proteomics using high-performance liquid chromatography combined with tandem mass spectrometry (LC-OrbiTrap LTQVelos, ThermoFisher Scientific). A total of 141 (biotinylation), 98 (shaving) and 910 (fractionation) proteins were identified. Throughout the 920 unique proteins identified, many are connected to basic cell functions, but some are linked with thermoregulation. We observed some noteworthy protein abundance shifts associated with the major adaptation to cold mechanisms present in L. monocytogenes, namely: the role of ribosomes and the stressosome with a higher abundance of the general stress protein Ctc (Rl25) and the general stress transcription factor sigma B (σB), changes in cell fluidity and motility seen by higher levels of foldase protein PrsA2 and flagellin (FlaA), the uptake of osmolytes with a higher abundance of glycine betaine (GbuB) and carnitine transporters (OpucA), and the relevance of the overexpression of chaperone proteins such as cold shock proteins (CspLA and Dps). As for 37°C, we observed a significantly higher percentage of proteins associated with transcriptional or translational activity present in higher abundance upon comparison with the colder settings. These contrasts of protein expression throughout several conditions will enrich databases and help to model regulatory circuitry that drives adaptation of L. monocytogenes to environments.